MAGNETIC-PROPERTIES OF FE73.5CU1NB3(SIXB1-X)22.5 (X=0.5-0.8) ALLOYS WITH ULTRAFINE GRAIN STRUCTURES - NOH, TH; PI, WK; KIM, HJ; KANG, IK (AMER INST PHYSICS, 1991)
The metalloid effect on magnetic properties and microstructures of iron-based alloys with ultrafine grain structures was investigated. For Fe73.5Cu1Nb3(Si(x)B1-x)22.5 (0.5 less-than-or-equal-to x less-than-or-equal-to 0.8) alloys with 10-15-nm grain diameters, the permeability increased with Si content. The alloys with x = 0.5 and 0.6 subjected to the optimum heat treatment had two different ferromagnetic phases which were composed of an alpha-Fe(Si) solid solution with high Curie temperature and an interfacial phase with low Curie temperature. However, in high Si alloys with x = 0.7 and 0.8, only a phase with high Curie temperature appeared. This results suggests that in the high Si composition range, a complete transformation from the amorphous phase to the alpha-Fe(Si) single phase was achieved. The disappearance of the interfacial phase which would certainly disturb the exchange coupling between the alpha-Fe(Si) phase grains would be considered to be one of the factors for the increased permeability.
Keywords: CRYSTALLIZATION